Fundamentals of food process engineering - Romeo T. Toledo. (Van Nostrand Reinhold, 2007)
This edition features the addition of sections on freezing, pumps, the use of chemical reaction kinetic date for thermal process optimization, and vacuum belt drying. New sections on accurate temperature measurements, microbiological inactivation curves, inactivation of microorganisms and enzymes, pasteurization, and entrainment are included, as are non-linear curve fitting and processes dependent on fluid film thickness. Other sections have been expanded.